2019
DOI: 10.1097/meg.0000000000001479
|View full text |Cite
|
Sign up to set email alerts
|

Stress and a sedentary lifestyle are associated with irritable bowel syndrome in medical students from Peru: a cross-sectional study

Abstract: Background Previous studies suggest that medical students may have higher rates of irritable bowel syndrome as compared to the general population. We hypothesized lifestyle characteristics may be associated to irritable bowel syndrome. Methods A cross-sectional survey was conducted in 2015 among students in their fourth, fifth, sixth and seven years of a medical school in Peru. Volunteer participants responded to questions pertaining to demographics, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
1
21
0
2
Order By: Relevance
“…For example, using the rome iv criteria, an Indian study showed that FD and IBS were the most frequent FGIDs [ 2 ]. Medical students seem to be at increased risk of developing FGIDs compared to their non medical counterparts [ 20 , 23 , 24 ], this appears to be especially true as students progress through medical school [ 25 , 26 ]. This, however, remains subject of controversy; with some studies reporting increased prevalence of FGIDs with increased level of studies [ 25 , 26 ] while others showing that neither the level of studies, nor the medical curriculum compared to other non-medical curriculums do influence the prevalence of FGIDs [ 13 , 21 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, using the rome iv criteria, an Indian study showed that FD and IBS were the most frequent FGIDs [ 2 ]. Medical students seem to be at increased risk of developing FGIDs compared to their non medical counterparts [ 20 , 23 , 24 ], this appears to be especially true as students progress through medical school [ 25 , 26 ]. This, however, remains subject of controversy; with some studies reporting increased prevalence of FGIDs with increased level of studies [ 25 , 26 ] while others showing that neither the level of studies, nor the medical curriculum compared to other non-medical curriculums do influence the prevalence of FGIDs [ 13 , 21 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…All can move spleen dampness, which makes it clear that diarrhea is mostly caused by exogenous or internal causes of spleen dampness. “Danxi heart method diarrhea”: “wet diarrhea, from sitting in a wet place, so that dampness hurts the spleen, soil cannot control water, there are many of this disease, it is appropriate to remove dampness soup to swallow Wuji pills, supplemented with Weiling decoction.” In the treatment, put forward that more because of dampness, but benefit small water, is the best policy, that is, to urinate, so real defecation [ 24 ]. Zhi Ming Zhang Jiebin made it clear that “the treatment of diarrhea is disadvantageous to small water, not its treatment.” Li Dongyuan, a member of the soil-tonifying faction, believes that diarrhea is caused by damage to the spleen and stomach in the final analysis.…”
Section: Discussionmentioning
confidence: 99%
“…15 In studies conducted with medical students using Rome III criteria, the IBS prevalence was found as 9.5% in Peru, 21% in Saudi Arabia, 31.7% in Egypt, and 33.3% in China. 8,9,16,17 In recent studies conducted by using the Rome IV criteria, IBS prevalence among medical students was found to be 14.7% in Malaysia and 14% in Benin, and 31.9% in Saudi Arabia. 10,18,19 Different results in countries may be due to differences in genetic, cultural, nutritional, and study methodology.…”
Section: Discussionmentioning
confidence: 99%